Pentingnya Komitmen Organisasi Dan Teknologi Informasi Dalam Upaya Menunjang Strategi Peningkatan Kinerja Karyawan Pada PT. Eriadi Fatkhur Rokhman Kantor Jasa Akuntan Medan - Chessara Addina; Juliana Nasution (Jurnal AKMAMI (Akuntansi Manajemen Ekonomi), 2022)
The success of a company really depends on organizational commitment that involves leaders to guide and build team work, in terms of modernizing the way of working, expanding new partners, adapting to the digitalization era and maintaining integrity. The rapid progress and sophistication of the use of information technology as a factor affecting employee performance as ownership of access and networking because technology is a necessity, technology makes it easier, technology protects and technology is a selling point. Employee performance is one of the company's most important vital assets because its role in strategy implementation is very important, namely as the implementing subject of organizational strategy. This study has a purpose, namely to find out how the relationship between organizational commitment and information technology in an effort to support the strategy of improving employee performance at PT. Eriadi Fatkhur Rokhman Medan Accountant Services Office. This study uses a qualitative descriptive research method.